2006
DOI: 10.1007/s10482-005-9024-z
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptomic analysis of Desulfovibrio vulgaris on different electron donors

Abstract: Whole-genome microarrays of Desulfovibrio vulgaris were used to determine relative transcript levels in cells grown to exponential or stationary phase on a medium containing either lactate or formate as electron donor. The results showed that 158 and 477 genes were differentially expressed when comparing exponential to stationary phase in lactate- or formate-based media, respectively; and 505 and 355 genes were responsive to the electron donor used at exponential or stationary phase, respectively. Functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 37 publications
6
36
0
Order By: Relevance
“…Despite trace concentrations of sulfate in the growth medium, key genes for sulfate respiration (genes encoding ATP sulfurylase, adenylyl-sulfate reductase, dissimilatory sulfite reductase, pyrophosphatase, and thiosulfate reductase) were also upregulated during syntrophic growth, consistent with previous observations of constitutive expression (13,49). However, none of the sulfate permease genes were upregulated, and one (DVU0053) was significantly downregulated.…”
Section: Resultssupporting
confidence: 88%
“…Despite trace concentrations of sulfate in the growth medium, key genes for sulfate respiration (genes encoding ATP sulfurylase, adenylyl-sulfate reductase, dissimilatory sulfite reductase, pyrophosphatase, and thiosulfate reductase) were also upregulated during syntrophic growth, consistent with previous observations of constitutive expression (13,49). However, none of the sulfate permease genes were upregulated, and one (DVU0053) was significantly downregulated.…”
Section: Resultssupporting
confidence: 88%
“…Thus, formate induces higher expression of this enzyme in the presence of both Mo and W, whereas hydrogen leads to a strong increase in expression only in the presence of W, suggesting that the interplay between regulation by the metals and the growth substrates is different for formate relative to lactate or H 2 . Previous microarray experiments have already reported that formate and hydrogen lead to increased expression of the three FDHs in D. vulgaris relative to lactate (34,53). Overall, the qRT-PCR results for the FdhAB fdhB mRNA levels are in agreement with the protein levels and activity results and suggest that tungsten is an inducer of FdhAB gene expression.…”
supporting
confidence: 84%
“…Notably, when cells were grown with formate or hydrogen, there was a very high increase in activity when Mo was replaced with W, and this effect was more pronounced in the soluble fraction than in the membrane fraction. The higher activities of cells grown with formate, and particularly with hydrogen, are in line with the reported higher expression of the D. vulgaris FDH genes during growth with these electron donors than that with lactate (34,53). For these two conditions, we also tested the simultaneous addition of both metals or no addition.…”
Section: Effect Of Mo and W On D Vulgaris Growth And Fdh Activitiessupporting
confidence: 72%
“…Most recent studies have either failed to find a significant correlation between protein and mRNA abundances (Gygi et al, 1999) or have observed only a weak correlation (Ideker et al, 2001;Greenbaum et al, 2002;Washburn et al, 2003;Zhang et al, 2006b;Nie et al, 2007). It has been suggested that the discrepancy arises from several factors, including protein regulation by post-translational modification, posttranscriptional regulation of protein synthesis, differences in the half-lives of mRNA and proteins, possible functional requirement for protein binding, and significant levels of experimental error (Greenbaum et al, 2002;Beyer et al, 2004;Park et al, 2005).…”
Section: Integrated Transcriptomics and Proteomicsmentioning
confidence: 99%